The hare and the tortoise - Sandford, John. (Reading, Mass. Addison-Wesley, 1989)
A big book version of the story of the race between the boastful hare and the persevering tortoise.
Keywords: Fables; Tortoise -- Juvenile fiction; Hare -- Juvenile fiction